Storage and Packaging Studies on Degermed Maize Flour - Houssou, P.A.F. (University of Ghana, 2000)
degermed maize flour (control). The percentage fat, ash, and fiber content were 1.42 } 0.34, 0.2 } 0.03, and 0.51 } 0.01 respectively for degenned maize flour and 6.02 } 0.63, 1.51 } 0.16, and 1.84 } 0.05 for non-degenned flour. Carbohydrate content was relatively higher (79.96%) in degenned maize flour than in the non-degermed maize flour which was 74.14% as a result of germ and hull. The moisture sorption isotherm of degermed maize flour (DF) and nondegermed maize flour (nDF) followed a type (II) isotherm pattern (Labuza,1984). The water absorption pattern of DF and nDF in relation to the various Water Activities (Aw) was higher for DF as compared to nDF at Aw between 0.11 to 0.71 indicating that the DF is more hygroscopic. DF showed a higher monolayer value of 3 .9g/l 00 solid matter as compared to nDF which was 2.98 g/100 solid matter. The heat of sorption of DF and nDF decreased with increasing moisture concentration. But at low Aw ranging from 0.11 to 0.44 the total heat of sorption of nDF is higher than that o f DF. Water vapor permeability test conducted on packaging materials used, showed that low Density Polyethylene has a higher water vapor transmission rate than Polypropylene (PP) and High Density (HD) which had s imilar rates. The initial moisture content of the flour samples ranged between 10.39 } 0.49% (solar dried sample) and 10.74 } 0.87% (Oven dried sample) for nDF, and 11.0 } 0.6 % (solar dried sample) and 10.57 } 0.78 % (Oven dried sample) for DF when packaged in HD and PP packaging materials and stored at 29 } 1°C. After.six months storage period, the final moisture content attained by both flour samples were between 10.63 } 0.63 % (Solar dried sample) and 12.61 } 0.77% (Oven dried sample) for nDF and 12.37 } 0.31% (Oven dried sample) and 11.27 } 0.48% (solar dried sample) for DF. These values are less than 13% moisture standard set for the storage of cereal flour (Kent, et al., 1970). After 6 months storage the non-degermed maize flour samples showed high percentage free fatty acid content (0.54 } 00 %) as compared to degermed maize flour samples (0.44 } 00 %) owing to the initial differences of fat content of the flour samples. Based on the results obtained it can be concluded that degermed maize flour can be stored for at least 6 months or longer with minimal changes in quality; and that the degermed maize flour has a higher potential for storage than the non-degermed maize flour.
Thesis (MPhil) - University of Ghana, 2000